Effects of lipid emulsion particle size on satiety and energy intake: a randomised cross-over trial. Issue 3 (March 2018) - Poppitt, Sally; Budgett, Stephanie; MacGibbon, Alastair; Quek, Siew-Young; Kindleysides, Sophie; Wiessing, Katy
Abstract Background/objectives Emulsified lipids, with central lipid core surrounded by polar lipid 'protective coat', have been proposed to stimulate the ileal brake, alter appetite, food intake and aid weight control. In addition to lipid composition, emulsion particle size may contribute to efficacy with small droplets providing a larger surface area for gastrointestinal (GI) lipase action and larger droplets prolonging and delaying digestion in the GI tract. Tube feeding studies delivering emulsions directly into the small intestine show clear effects of smaller particle size on appetite and food intake, but evidence from oral feeding studies is sparse. The objective of this study was to determine the effects of lipid emulsion particle size on appetite response and food intake. Subjects/methods In a three-arm randomised cross-over, high-phospholipid (PL) dairy lipid emulsions or matched control were consumed at breakfast within a yoghurt smoothie: (i) large-particle size emulsion, LPE (diameter 0.759 µm, 10 g lipid emulsion, 190 g yoghurt), (ii) small-particle size emulsion, SPE (diameter 0.290 µm, 10 g lipid emulsion, 190 g yoghurt), (iii) control non-emulsion, NE (10 g non-emulsion lipid, 190 g yoghurt). Twenty male participants completed the study, where postprandial appetite response was rated using visual analogue scales (VAS) andad libitum energy intake at a lunch meal measured 3 h later. Results There was a trend for LPE to suppress hunger (P = 0.08) and enhance fullness (P = 0.24) relative to both SPE and NE but not statistically significant, and no significant effect of either emulsion on food intake at the lunch meal (P > 0.05). Conclusions Altering particle size of a high-PL emulsion did not enhance satiety or alter eating behaviour in a group of lean men.